Elaboration, development, and installation of the first animal skin bank in Brazil for the treatment of burns and wounds - Edmar Maciel Lima; Manoel Odorico Moraes-Filho; Marina Becker Sales Rocha; Francisco Raimundo Silva-Júnior; Cybele Maria Philopimin Leontsinis; Maria Flaviane Araújo do Nascimento (Revista Brasileira de Cirurgia Plástica, 2019)
Introduction: The production and distribution of human skin by Brazilian skin banks is insufficient to meet the country's demand, supplying less than 1% of the need for treating burn victims. The objective of this work was to present the elaboration and development of the first animal skin bank of Brazil for the treatment of burns. Methods: This methodological study elaborated, developed, and installed The Aquatic Animal Skin Bank in terms of the development of tilapia skin processing after a systematic review of studies referring to animal skin banks based on visits to the pisciculture center in Jaguaribara-CE, technical visits to human skin banks in Brazil, technical consultation and training in the Recife Skin Bank, the observation of all phases of tilapia skin processing, and the identification of the physical structure of the area where the processes occur. Results: In addition to the production and distribution of tilapia skin for studies on burn victims, the bank is processing more than 5000 tilapia skin samples and is in the distribution phase of this skin for multicentric studies in other states and specialties including gynecology, orthopedics, endoscopy, stomatherapy, vascular surgery, dentistry, and veterinary medicine. Conclusion: This work enabled the elaboration, development, and implementation of Brazil's first animal skin bank and the world's first aquatic skin bank.